2008
DOI: 10.1186/1471-2334-8-21
|View full text |Cite
|
Sign up to set email alerts
|

Transmitted drug resistance, selection of resistance mutations and moderate antiretroviral efficacy in HIV-2: Analysis of the HIV-2 Belgium and Luxembourg database

Abstract: Background: Guidelines established for the treatment of HIV-1 infection and genotype interpretation do not apply for HIV-2. Data about antiretroviral (ARV) drug efficacy and resistance mutations is scarce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 47 publications
2
35
0
1
Order By: Relevance
“…Furthermore, the addition of K65R, Q151M, or both in combination with M184V did not lead to higher levels of MK-8591 resistance than with M184V alone. This result is significant given the frequent appearance of K65RϩM184V, Q151MϩM184V, and K65RϩQ151MϩM184V variants in HIV-2-infected patients (9,36,44,48,49). We speculate that, relative to 3TC/FTC, MK-8591 might delay the appearance of M184V in both HIV-1-and HIV-2-infected patients and, in the event of its emergence, retain substantial activity against the mutant virus.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Furthermore, the addition of K65R, Q151M, or both in combination with M184V did not lead to higher levels of MK-8591 resistance than with M184V alone. This result is significant given the frequent appearance of K65RϩM184V, Q151MϩM184V, and K65RϩQ151MϩM184V variants in HIV-2-infected patients (9,36,44,48,49). We speculate that, relative to 3TC/FTC, MK-8591 might delay the appearance of M184V in both HIV-1-and HIV-2-infected patients and, in the event of its emergence, retain substantial activity against the mutant virus.…”
mentioning
confidence: 77%
“…It is important to note that the EC 50 s for all HIV-2 ROD9 clones containing M184V (with or without other changes) were only 2-to 4-fold greater than the mean EC 50 for HIV-1 isolates from ART-naive individuals (2.6 nM). Although we cannot exclude the possibility that other amino acid replacements in HIV-2 RT confer higher levels of MK-8591 resistance, our analysis demonstrates that MK-8591 retains substantial activity against the types of drug-resistant variants that typically emerge in NRTI-treated HIV-2 patients (9,10,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We found that this change, which was among the most common "primary" substitutions observed in our cohort, caused substantial resistance to DRV but only low-level resistance to LPV in HIV-2. Previous reports have concluded that in HIV-2, L90M can emerge in response to virtually all PIs (30,34,35). L90M in HIV-1 confers resistance to SQV and is a secondary change affecting susceptibility to LPV.…”
Section: Discussionmentioning
confidence: 99%
“…Although the changes that confer resistance to these and other PIs are well documented in HIV-1 (27), data defining PI resistance pathways in HIV-2 are extremely limited. Studies comparing HIV-2-infected ART-treated subjects to naive subjects have provided evidence of a variety of PI-associated changes (9,(28)(29)(30)(34)(35)(36), and in our cohort of IDV-and/or LPV/r-treated Senegalese HIV-2-infected subjects, we observed several substitutions that are known to be primary PI resistance-conferring changes in HIV-1, including V47A, I54M, I82F, I84V, and L90M. Our analysis of site-directed HIV-2 mutants shows that V47A, I54M, and L90M confer phenotypic patterns similar to those seen in HIV-1, with significant resistance to one or more PIs.…”
Section: Discussionmentioning
confidence: 99%